HEALTHTECH STARTUPS INTERNAL CONTROL TO INCREASE COMPETITIVE ADVANTAGE IN THE NEW NORMAL ERA - Aulia Nurazizah; Novita Novita (Jurnal Akuntansi, 2021)
This research aims to prove the positive influence of the implementation of COSO internal control on increasing competitive advantage in health startups in the New Normal Era. This research is a quantitative study using primary data in the form of questionnaires and secondary data in the form of online interviews. The unit of research is a health start-up, namely the Halodoc Application. The population in this study were users of the Halodoc Application and then the research sample was taken using nonprobability sampling techniques. So that the number of samples processed for analysis is 100 samples. The data analysis technique used descriptive analysis and verification methods. The results showed that the implementation of COSO internal control implemented by the Halodoc Application had a positive effect in increasing competitive advantage.